Penerapan Sistem Informasi Pendaftaran Peserta Didik Baru Berbasis WEB Untuk Peningkatan Mutu dan Jumlah Pendaftar - Wawan Nugroho (Fakultas Teknik Universitas Hamzanwadi, 2023)
Technological advancements that affect all aspects of life serve as guidelines for resolving existing issues. Technological developments facilitate daily activities in various fields such as education, politics, social, and others. In the world of education, competition has created intense competition between schools. As a result, technological advancements must be followed by educational institution processing. The existence of schools plays an important role in the process of inputting data. This study uses the waterfall method in designing a new student registration system. The design begins with analysis, then moves on to design, coding, and testing. The developed web-based system uses the CodeIgniter Framework with the PHP (Hypertext Preprocessor) programming language and MySQL as the database. The stages of testing the website using black box testing before the system is used show that the website is running according to its functionality. The results of the developed website are able to assist in managing new student registration data and can make direct reports so that management becomes effective and efficient